Cover Image. Issue 2 (24th June 2022) - Zheng, Xunchen; Hu, Tianjiang
Abstract : The cover image is based on the Research Article Air2Land: A deep learning dataset for unmanned aerial vehicle autolanding from air to land by Tianjiang Hu et al., https://doi.org/10.1049/csy2.12045 .